2007
DOI: 10.1021/jf071689v
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Antioxidant Activity of a Pomegranate Ellagitannin-Enriched Polyphenol Dietary Supplement in Overweight Individuals with Increased Waist Size

Abstract: The consumption of pomegranate juice (PJ), a rich source of antioxidant polyphenols, has grown tremendously due to its reported health benefits. Pomegranate extracts, which incorporate the major antioxidants found in pomegranates, namely, ellagitannins, have been developed as botanical dietary supplements to provide an alternative convenient form for consuming the bioactive polyphenols found in PJ. Despite the commercial availability of pomegranate extract dietary supplements, there have been no studies evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(131 citation statements)
references
References 7 publications
2
121
4
1
Order By: Relevance
“…Previous studies by our group have demonstrated that pomegranate extract is well-tolerated and without significant gastrointestinal or systemic toxicity after ingesting two 1000 mg capsules per day [15]. We also showed no difference in pharmacokinetics of plasma ellagic acid metabolites between pomegranate juice and extract [28].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies by our group have demonstrated that pomegranate extract is well-tolerated and without significant gastrointestinal or systemic toxicity after ingesting two 1000 mg capsules per day [15]. We also showed no difference in pharmacokinetics of plasma ellagic acid metabolites between pomegranate juice and extract [28].…”
Section: Discussionsupporting
confidence: 70%
“…The total phenolics content of the POMx and POM juice was determined using the Folin-Ciocalteau colorimetric method [14] and reported as gallic acid equivalent (GAE). The polyphenol composition of the POMx solution and POM juice was determined by HPLC as previously described [15,16].…”
Section: Phytochemical Preparationsmentioning
confidence: 99%
“…However, a more robust protection may result from exploiting the endogenous antioxidant response. Botanical compounds that activate Nrf2 are actively being tested for their therapeutic efficacy in other diseases involving oxidative damage, including cancer and cardiovascular disease (2,14,28,40,49,69). We recently identified a panel of compounds that prevent glucose-induced mitochondrial oxidative stress and injury in DRG neurons (78), but their effects on Nrf2 are not known.…”
mentioning
confidence: 99%
“…Only Kannan and Quine (2011) found that pretreatment with the basic component of ellagitannins, ellagic acid, prevents isoproterenol-induced oxidative stress and decreased HCy level in myocardial infarction in rats. In a number of other human studies some positive effects were found on markers of oxidative stress (increased activity of PON1, reduced TBARP in serum, reduced 8-oxo-dG level) or on lipid profile (Aviram et al 2000;Cerdá et al 2004;Pantuck et al 2006;Heber et al 2007;Rock et al 2008;Fuhrman et al 2010;Larrosa et al 2010;López-Uriarte et al 2010). Positive effects were not observed after ellagic acid or ellagitanins supplementation on inflammatory markers (IL-6 and CRP) (Trombold et al 2010) and on cholesterol level in subjects with metabolic syndrome (Casas-Agustench et al 2010).…”
Section: Discussionmentioning
confidence: 98%